Clinical and occupational risk factors for coronavirus disease 2019 (COVID-19) in healthcare personnel - Jennie H. Kwon; Philip J. Budge; Caroline A. O'Neil; Kate Peacock; Eva M. Aagaard; Victoria J. Fraser; Margaret A. Olsen; Hilary Babcock; for the CDC Prevention Epicenters Program (Cambridge University Press, 2022)
Abstract Objective: To identify characteristics associated with positive severe acute respiratory coronavirus virus 2 (SARS-CoV-2) polymerase chain reaction (PCR) tests in healthcare personnel. Design: Retrospective cohort study. Setting: A multihospital healthcare system. Participants: Employees who reported SARS-CoV-2 exposures and/or symptoms of coronavirus disease 2019 (COVID-19) between March 30, 2020, and September 20, 2020, and were subsequently referred for SARS-CoV-2 PCR testing. Methods: Data from exposure and/or symptom reports were linked to the corresponding SARS-CoV-2 PCR test result. Employee demographic characteristics, occupational characteristics, SARS-CoV-2 exposure history, and symptoms were evaluated as potential risk factors for having a positive SARS-CoV-2 PCR test. Results: Among 6,289 employees who received SARS-CoV-2 PCR testing, 873 (14%) had a positive test. Independent risk factors for a positive PCR included: working in a patient care area (relative risk [RR], 1.82; 95% confidence interval [CI], 1.37-2.40), having a known SARS-CoV-2 exposure (RR, 1.20; 95% CI, 1.04-1.37), reporting a community versus an occupational exposure (RR, 1.87; 95% CI, 1.49-2.34), and having an infected household contact (RR, 2.47; 95% CI, 2.11-2.89). Nearly all HCP (99%) reported symptoms. Symptoms associated with a positive PCR in a multivariable analysis included loss of sense of smell (RR, 2.60; 95% CI, 2.09-3.24) or taste (RR, 1.75; 95% CI, 1.40-2.20), cough (RR, 1.95; 95% CI, 1.40-2.20), fever, and muscle aches. Conclusions: In this cohort of >6,000 healthcare system and academic medical center employees early in the pandemic, community exposures, and particularly household exposures, were associated with greater risk of SARS-CoV-2 infection than occupational exposures. This work highlights the importance of COVID-19 prevention in the community and in healthcare settings to prevent COVID-19.